Experimental analysis and design strength models adopted by international guides for FRP-confined concrete columns subjected to axial compression - J.P. Gutiérrez (Consejo Superior de Investigaciones Científicas, 2021)
Carbon fiber jacketing is an efficient technique for increasing the strength and strain capacity of concrete circular and square section columns subjected to axial load, although confinement efficiency decreases for rectangular cross-section members. The research project BIA 2016-80310-P includes an experimental program on intermediate-size plain concrete specimens strengthened with carbon fiber jackets, mostly with square and rectangular cross-sections. The results, alongside others with similar characteristics from two databases published, are compared to predictions of four international guides. The incidence of the key parameters in the experimental results is analyzed, such as the aspect ratio of the section, the effective strain in FRP jacket attained at failure or the rounded corner radius. As a result, two efficiency strain factors are proposed, one for circular and another for rectangular specimens. The predictions contained in certain guides, based on a simple linear design-model, are improved by using the proposed efficiency strain factor for rectangular sections.